Pengaruh Perencanaan, Pelaksanaan, Pelaporan dan Evaluasi Anggaran Berbasis Kinerja terhadap Akuntabilitas Kinerja pada Politeknik Negeri Malang - Atika Syuliswati; Andi Asdani (STIE Malangkucecwara, 2017)
This study aims to give empirical evidence of the application performance-based budgeting affect to performance accountability at State Polytechnic Of Malang, to see the effect of the application of performance-based budgeting to performance accountability using four variables namely, budgeting planning, budgeting implementation, budgeting reporting, and budgeting evaluation. In this study population taken were 49 people, they are director, deputy director, head of department, secretary of department, head of study program, head of technical unit and there are whole sample. Data collected through direct observation and surveys obtained by the division of questionnaires to the respondents. Multiple linear regression formula is used in this study with software SPSS 20.0. The results of this research proves that simultaneously budgeting planning, budgeting implementation, budgeting reporting, and budgeting evaluation have a significant and positive effect to performance accountability. Partially budgeting planning and budgeting reporting have significant and positive effect to performance accountability.